1989
DOI: 10.1203/00006450-198904000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Ontogeny in the Ovine Fetus: XIX: The Effect of a Potent Luteinizing Hormone-Releasing Factor Agonist on Gonadotropin and Testosterone Release in the Fetus and Neonate'

Abstract: To investigate further the role of the hypothalamic luteinizing hormone releasing factor (LRF) pulse generator and the pituitary LRF receptor in the regulation of gonadotropin secretion and gonadal steroidogenesis in the ovine (O) fetus and neonatal lamb, we measured the increment (the difference between the concentration of plasma LH at time 0 and peak LH) in oLH (delta oLH) and oFSH (delta oFSH) responses to a potent LRF agonist, D-Trp6Pro9NEt-LRF (LRF-A), after consecutive daily doses in 17 ovine fetuses (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It has been established in the sheep fetus that LH is secreted in a pulsatile manner at least from 81 days of gestation [29]. Moreover, the release of LH is suppressed by an infusion of a GnRH agonist [30] or antagonist at least from 104 days of gestation [31]. Furthermore, the sensitivity of the fetal pituitary to exogenous GnRH is maximal between 115 and 132 days of gestation [32].…”
Section: Discussionmentioning
confidence: 98%
“…It has been established in the sheep fetus that LH is secreted in a pulsatile manner at least from 81 days of gestation [29]. Moreover, the release of LH is suppressed by an infusion of a GnRH agonist [30] or antagonist at least from 104 days of gestation [31]. Furthermore, the sensitivity of the fetal pituitary to exogenous GnRH is maximal between 115 and 132 days of gestation [32].…”
Section: Discussionmentioning
confidence: 98%
“…At this gestational age, the gonadotropin response to exogenous LHRH is less than that during midgestation, when the mean basal plasma concentrations of oLH and oFSH are high [3]. We showed that specific high-affinity LH-RH receptors are present by midgestation in the ovine fetal pituitary and that the high oLH and oFSH plasma values are LH-RH dependent [4]. Hence the fetal hypothalamic LH-RH-pituitary gonadotropin-gonadal system is functional as early as midgestation.…”
Section: Discussionmentioning
confidence: 99%
“…In the primary pituitary cell culture system, NMDA had no effect on oLH, oFSH, oGH, and oPRL secretion, while LH-RH stimulated both oLH and oFSH. Furthermore, desensitization of the fetal gonadotropes with D -Trp 6 Pro 9 NEt-LH-RH, which suppresses fetal pituitary gonadotropins and the response to exogenous LH-RH [4], completely abolished the oLH and oFSH responses to the administration of NMDA. Neuroexcitatory amino acids also failed to stimulate LH and FSH release when they were incubated with pituitary tissue from adult rats and monkeys [15, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that circulating levels of LH and FSH in male and female fetuses during mid gestation were similar to those observed in castrated adult sheep. Moreover, sequential sampling of the fetal circulation identified distinct episodes of GnRH dependent LH secretion at this stage of fetal development presumable reflecting corresponding discharges of GnRH from the fetal hypothalamus [152] [153]. The latter view is supported by the contemporaneous finding that administration of an iv bolus of the GnRH secretagogue, NMDA (see above) elicited LH discharges from the fetal pituitary [154].…”
Section: Reverse Translation Of the Primate Modelmentioning
confidence: 99%